Laparoscopic-Assisted Transgastric ERCP: A Single-Institution Experience - Katherine Habenicht Yancey; Lauren Katherine McCormack; Stephen Samuel McNatt; Myron Sheavictor Powell; Adolfo Zachariah Fernandez; Carl Joseph Westcott (Journal of Obesity)
Background. Laparoscopic-assisted transgastric endoscopic retrograde cholangiopancreatography (LAERCP) is used for treatment in patients after Roux-en-Y gastric bypass (RYGB), where transoral access to the biliary tree is not possible. We describe our technique and experience with this procedure. Methods. Electronic medical record search was performed from September 2012 to January 2016, identifying patients who underwent LAERCP per operative records. Charts were reviewed for demographic, clinical, and outcomes data. Results. Sixteen patients were identified. Average time since bypass was 6.9 years, and length of stay was 3.7 days. Five patients underwent simultaneous cholecystectomy. Eleven patients, or 43%, had cholecystectomy more than 2 years previously. ERCP with sphincterotomy was completed in 15 of 16 patients (94%). Our technique involves access to the bypassed stomach via a laparoscopically placed 15 mm port. We observed one major complication of post-ERCP necrotizing pancreatitis. No minor complications nor mortalities were seen in our series. Conclusion. Biliary obstruction can occur many years after RYGB and cholecystectomy. Our findings suggest that RYGB patients may be at a higher risk of primary CBD stone formation. LAERCP is a reliable option for common bile duct (CBD) clearance; our technique of LAERCP is technically simple and associated with low complication rate, making it appealing to surgeons not trained in advanced laparoscopy.